THE DEVELOPMENT OF A COMPREHENSIVE APPROACH TO THE PROBLEM OF REPLACING THE ACTIVE PART OF FIXED ASSETS ON THE BASIS OF MATHEMATICAL MODELING - Demjaniuk, E. S. (Science and Transport Progress, 2007)
The complex approach to the decision-making of renewal of an active part of a capital assets is developed. The basic stages and the control information of process of making of the investment decision are specified. Mathematical methods of the solution of the corresponding subproblems, raising efficiency of administrative decisions and lowering investment risks are determined. The information model of decision-making process is developed on the basis of the technology of functional modeling IDEF0.